Neural correlates of attentional bias in addiction. (6th August 2013) - Hester, Robert; Luijten, Maartje
Abstract : A small but growing neuroimaging literature has begun to examine the neural mechanisms underlying the difficulty that substance-use dependent (SUD) groups have with ignoring salient, drug-related stimuli. Drug-related attentional bias appears to implicate the countermanding forces of cognitive control and reward salience. Basic cognitive neuroscience research suggests that ignoring emotionally evocative stimuli in our environment requires both up-regulation of control networks and down-regulation of processing in emotion and reward regions. Research to date suggests that attentional biases for drug-related stimuli emerge from a failure to sufficiently increase control of attention over salient, but task-irrelevant stimuli. While SUD samples have typically shown increased activity in the cognitive control regions (ie, lateral prefrontal and dorsal anterior cingulate), during attentional bias such increases appear to have been insufficient for the concomitant increases in processing by the emotion/reward regions (ie, amygdala, insula, and striatum). Given the potential contribution of attentional biases to perpetuating drug use and the development of interventions (both pharmaceutical and cognitive-behavioral) to treat biases, understanding the neural basis of successfully reducing bias remains an important, but as yet unanswered, question for our field.